PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 50 BABUSSALAM - Silvia Hasti; Atma Murni; Suhermi Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research aims to improve the learning process and improve learning outcomes of mathematics class of fifth SDN 50 Babussalam by implementing cooperative learning in the structural approach Two Stay Two Stray (TSTS). The subjects of the research were the fifth grade students SDN 50 Babussalam who have the heterogeneous academic ability. This research is a class act with two cycles. Each cycles has four stages. There are planning, implementation, observation, and reflection. The result of the observation show the teachers and students activities have done after the action. Increasing the number of students who achieve at UH KKM in every end of each cycle compared to the number of the students who achieve a score of KKM on basic score. The results of this study indicate that application of cooperative learning in the structural approach TSTS can improve the process of learning and improve the learning outcomes of fifth grade of mathematics students at SDN 50 Babussalam in the odd semester of academic year 2013/2014. Key words: Mathematics learning outcomes, Cooperative learning, Two Stay Two Stray (TSTS), Classroom action research.